2011
DOI: 10.1177/0741932510395397
|View full text |Cite
|
Sign up to set email alerts
|

Using In-Service and Coaching to Increase Teachers’ Accurate Use of Research-Based Strategies

Abstract: Increasing the accurate use of research-based practices in classrooms is a critical issue. Professional development is one of the most practical ways to provide practicing teachers with training related to research-based practices. This study examined the effects of in-service plus follow-up coaching on first grade teachers' accurate delivery of three researchbased strategies during math instruction. Teachers were trained to use a combination of whole-class instruction strategies, including model-lead-test for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 35 publications
3
52
0
1
Order By: Relevance
“…Both quantitative and qualitative research has found positive relationships between mathematics coaching and improved mathematics instruction (e.g., Alloway & Jilk, 2010;Baldinger, 2014;Campbell, 1996;Kretlow et al, 2012;Kretlow, Wood, & Cooke, 2011;Race, Ho, & Bower, 2002;Rudd, Lambert, Satterwhite, & Smith, 2009). Although the majority of studies conducted on mathematics coaches show the potential to influence teachers' instructional practices in a positive direction, results are influenced by the type and intent of the coach (e.g., Becker, 2001;McGatha, 2008) and teachers' varying experiences and ideas of how mathematics should be taught (e.g., Ai & Rivera, 2003;Olson and Barrett, 2004).…”
Section: Mathematics Coaching and Teacher Practicementioning
confidence: 99%
See 4 more Smart Citations
“…Both quantitative and qualitative research has found positive relationships between mathematics coaching and improved mathematics instruction (e.g., Alloway & Jilk, 2010;Baldinger, 2014;Campbell, 1996;Kretlow et al, 2012;Kretlow, Wood, & Cooke, 2011;Race, Ho, & Bower, 2002;Rudd, Lambert, Satterwhite, & Smith, 2009). Although the majority of studies conducted on mathematics coaches show the potential to influence teachers' instructional practices in a positive direction, results are influenced by the type and intent of the coach (e.g., Becker, 2001;McGatha, 2008) and teachers' varying experiences and ideas of how mathematics should be taught (e.g., Ai & Rivera, 2003;Olson and Barrett, 2004).…”
Section: Mathematics Coaching and Teacher Practicementioning
confidence: 99%
“…Although the list of roles and responsibilities of a MCS is abundant, the research on the effect of MCSs is sparse (e.g., NMAP, 2008;McGatha, 2009). That being said, recent research has shown that coaching is a promising practice and policy that could potentially advance instructional growth and teacher change (e.g., Campbell & Malkus, 2011;Kretlow et al, 2012;McGatha, 2009). …”
Section: Roles and Responsibilities Of Mcsmentioning
confidence: 99%
See 3 more Smart Citations